2016
DOI: 10.1080/03098265.2016.1154931
|View full text |Cite
|
Sign up to set email alerts
|

Ability of students to recognize the relationship between using mobile apps for learning during fieldwork and the development of graduate attributes

Abstract: Ability of students to recognize the relationship between using mobile apps for learning during fieldwork and the development of graduate attributes AbstractThe increasing importance of employability in Higher Education curricula and the prevalence of using mobile devices for field-based learning, prompted an investigation into student awareness of the relationship between the use of mobile apps for learning and the development of graduate attributes (and the link to employability). The results from post-fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…However, subsequently, recognising that 'Geographers learn through the soles of their feet', fieldwork became stablished as the heartwood of the Geography curriculum (McEwen, 1996;Lloyd et al, 2015, Gold et al, 1991. Martin Higgitt (1996b) Recently, such thinking has blossomed into writings that link fieldwork closely to the development of the general and discipline-specific 'graduate attributes' including emotional intelligence, critical thinking, problem solving and global citizenship (Couper & Porter, 2016;France et al, 2016;Fuller & France, 2016;Haigh, 2016;Hill, Walkington, & France, 2016;Spronken-Smith et al, 2016).…”
Section: Mode 4: Curriculum Centred ('Look Learn Do Use and Be Assmentioning
confidence: 99%
“…However, subsequently, recognising that 'Geographers learn through the soles of their feet', fieldwork became stablished as the heartwood of the Geography curriculum (McEwen, 1996;Lloyd et al, 2015, Gold et al, 1991. Martin Higgitt (1996b) Recently, such thinking has blossomed into writings that link fieldwork closely to the development of the general and discipline-specific 'graduate attributes' including emotional intelligence, critical thinking, problem solving and global citizenship (Couper & Porter, 2016;France et al, 2016;Fuller & France, 2016;Haigh, 2016;Hill, Walkington, & France, 2016;Spronken-Smith et al, 2016).…”
Section: Mode 4: Curriculum Centred ('Look Learn Do Use and Be Assmentioning
confidence: 99%
“…Using the hashtags at the end of the session to view a summary of student findings was useful and led to good discussion in the class. Similarly, France et al (2016) also noted that Twitter could lead to good communication between groups. However, Lackovic et al (2017) found that physiotherapy students did not engage well with Twitter in teaching sessions because the students considered it a career tool and in their first year this was too early to consider their careers.…”
Section: Discussionmentioning
confidence: 94%
“…Digital literacy is 'the capabilities which fit someone for living, learning, and working in a digital society' (Joint Information Systems Committee [JISC], 2014). Encouraging students to use their mobile devices in teaching sessions is one way to help achieve this (France et al, 2016;Woodcock, Middleton, & Nortcliffe, 2012). Social media enables students to demonstrate their digital literacy skills and showcase their interests and personalities on their social profiles (Ellison, Steinfield, & Lampe, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile devices have great potential to enhance undergraduate geography teaching, with recent studies focusing on the adoption of such devices by students in field locations (France et al, 2013;Welsh et al, 2015). This research has shown benefits in the form of enhanced data sharing and processing, post-fieldwork reflection and, more recently, development of graduate attributes (France et al, 2016;Fuller & France, 2016). Nevertheless, barriers to the use of mobile technology include cost and reliability/durability of devices, staff competence, and concern from some students that technology can distract them from their learning unless applied strategically and pedagogically (France et al, 2015).…”
Section: Looking To the Futurementioning
confidence: 99%